Four-step approach to idea management sequencing: Redefining or reinventing values in a business model - Elina Mikelsone; Inga Uvarova; Jean-Pierre Segers (Journal of Innovation and Entrepreneurship, 2022)
The purpose of this paper is to create and test an idea management sequence framework to reinvent or redefine the value proposition. Idea management with sequencing activities must be considered as a systematic managerial process and should not be confused with the occasional result of an individual with a design thinking mindset. This paper suggests a new approach-a systematic, 4-step idea management sequence to redefine or reinvent value proposition in a business model, which was validated through an action-based research method involving 20 managers from practice by applying the proposed framework. Based on the idea management approach, authors describe the idea generation and evaluation processes and their possible moderation elements. This research contributes to previous studies of the design thinking and innovation by substantiating a concept of the idea management sequencing and proposing a new 4-step approach that can be applied by organisations to redefine or reinvent value proposition in their business models. Being influenced by pandemic restrictions and the full or partial remote workforce, the 4-step idea management approach is beneficial for virtual group sessions as it increases the quality of outcomes, engagement of individuals, collaborative openness, and confidence.
Keywords: 650; Business model; Design thinking; Idea management; Ideation; Sequencing; Value proposition